If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6k + -3(k + 2) = (k + -2) Reorder the terms: 6k + -3(2 + k) = (k + -2) 6k + (2 * -3 + k * -3) = (k + -2) 6k + (-6 + -3k) = (k + -2) Reorder the terms: -6 + 6k + -3k = (k + -2) Combine like terms: 6k + -3k = 3k -6 + 3k = (k + -2) Reorder the terms: -6 + 3k = (-2 + k) Remove parenthesis around (-2 + k) -6 + 3k = -2 + k Solving -6 + 3k = -2 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. -6 + 3k + -1k = -2 + k + -1k Combine like terms: 3k + -1k = 2k -6 + 2k = -2 + k + -1k Combine like terms: k + -1k = 0 -6 + 2k = -2 + 0 -6 + 2k = -2 Add '6' to each side of the equation. -6 + 6 + 2k = -2 + 6 Combine like terms: -6 + 6 = 0 0 + 2k = -2 + 6 2k = -2 + 6 Combine like terms: -2 + 6 = 4 2k = 4 Divide each side by '2'. k = 2 Simplifying k = 2
| 8.4=-6g | | 9x+12=13x+24 | | 3(y-2)=6 | | 6n-4-3n=3n+10-4n | | 16w=4 | | 4x+12=13x+24 | | 5r-11=-15+9r | | 5x+-8y=11 | | x/27=4 | | A(w)=225w-w^2 | | -17.1=w/6+2.1 | | -11-4=-9 | | 1.3x-8= | | 35/8-2 | | x^2+3x+72=0 | | 5u-2.3=10.2 | | 12/18=x/3 | | 2x+7-4=13 | | 7x/8-9x/10=-3 | | 5(z+9)-9(z-7)= | | 6+y/-8=4/7 | | 9=5+u/10.24 | | c/3=-42 | | 6r+7=1.2 | | x/14=9/21 | | 5p^2-3p-36=0 | | 5n-3n+4=10 | | 2(4+x)=3x+8 | | 1/2=w-3/4 | | 4-3(x+3)= | | 3x/4=5x/2-7/2 | | 4x-3=12x+9 |